A late Permian palynological assemblage from the Spearfish Formation of South Dakota, United States: Implications for biostratigraphy, paleofloristics, and phytogeography - Hotton Carol, L.; Antoine, Bercovici; Looy Cindy, V.; Duijnstee Ivo, A.P.; Chaney Dan, S.; Eble Cortland, F.; Montañez Isabel, P.; Sylvie, Bourquin; Blaine, Cecil; John, Nelson; Gastaldo Robert, A.; Wingerath, J.; et al. (Palaeogeography, palaeoclimatology, palaeoecology, 2025)
We report here on a palynoflora from the Spearfish Formation of South Dakota that represents the first definite record of late Permian plant remains in the form of miospores from North America. The assemblage is dominated by taeniate pollen (Lueckisporites virkkiae, Lunatisporites noviaulensis, Corisaccites alutas, Jugasporites spp.) as well as simple saccate pollen taxa (Klausipollenites schaubergeri, Falcisporites spp.), but is highly depauperate in spores. The palynoflora was extracted from a mudstone associated with black fissile shales and carbonates about 30 m above the conformable contact with the underlying Minnekhata Limestone at Cascade Springs. Multiple lines of evidence from organic and carbonate petrology as well as acritarchs indicate that the depositional context was a brackish lagoon or inlet subject to high evaporation rates. Eolian dust, present in all studied units, combined with carbonate and organic petrography, indicates aridity through this interval. Through similarity and ordination analysis, we show that the Spearfish assemblage most closely resembles low paleolatitude palynofloras of late Permian (Lopingian) age in Europe and differs significantly from middle Permian palynofloras of the central United States. The palynoflora also differs from lower Triassic palynofloras, thereby establishing that the lower portion of the Spearfish Formation is late Permian. The similarity in composition of the Spearfish assemblage in the western United States to xeric European assemblages indicates that a near-uniform xerophytic flora dominated by voltzian conifers and peltasperms extended thousands of kilometers across low-latitude Pangaea in late Permian times. •Palynological data show that the lower third of the Spearfish Formation of South Dakota, U.S.A., is late Permian in age and closely correlates with low paleolatitude European palynofloras.•The Spearfish assemblage represents the first reported upper Permian plant microfossils or megafossils from the United States.•The Spearfish assemblage is distinct from middle Permian North American assemblages.•The palynological assemblage occurs within a sabkha-like lagoonal setting.•Palynology combined with stable carbon-and‑oxygen isotopic analysis, carbonate, organic petrography and mineralogical analyses of associated sediments indicate deposition in an arid environment.